«ЕР ЗИЙЎАР» ҲӘМ ҚАРАҚАЛПАҚ ҚАҲАРМАНЛЫҚ ДӘСТАНЛАРЫНЫҢ СЮЖЕТ ТИПОЛОГИЯСЫ - Бекбергенова, А.У. (ILIM hám JÁMIYET, 2024)
The article explores the plot typology of «Er Ziyuar» and the Karakalpak heroic epic. Based on the study, it is concluded that a comparative study of the plot typology of epics is important for determining the origin of the epic, genre features, and a deeper disclosure of its content.